Specialty Care Delivery: Bringing Infectious Disease Expertise to the Residents of a Veterans Affairs Long‐Term Care Facility. Issue 5 (16th April 2013) - Jump, Robin L. P.; Olds, Danielle M.; Jury, Lucy A.; Sitzlar, Brett; Saade, Elie; Watts, Brook; Bonomo, Robert A.; Donskey, Curtis J.
<x xml:space="preserve">Abstract</x> Objective To initiate a long‐term care facility (LTCF) infectious disease (LID) service that provides on‐site consultations to LTCF residents to improve the care of residents with possible infections. Design Clinical demonstration project. Setting A 160‐bed LTCF affiliated with a tertiary care Veterans Affairs (VA) hospital. Participants Residents referred to the LID team. Measurements The reason for and source of LTCF residents' referral to the LID team and their demographic characteristics, infectious disease diagnoses, interventions, and hospitalizations were determined. Results Between July 2009 and December 2010, the LID consultation service provided 291 consultations for 250 LTCF residents. Referrals came from LTCF staff (75%) or the VA hospital's ID consult service (25%). The most common diagnoses were Clostridium difficile infection (14%), asymptomatic bacteriuria (10%), and urinary tract infection (10%). More than half of referred residents were receiving antibiotic therapy when they first saw the LID team; 46% of residents required an intervention. The most common interventions, stopping (32%) or starting (26%) antibiotics, were made in accordance with principles of antibiotic stewardship. Conclusion The LID team represents a novel and effective means to bring subspecialty care to LTCF residents.